Mechanical properties of micro and sub-micron wollastonite fibers in cementitious composites. (1st May 2015) - Dey, V.; Kachala, R.; Bonakdar, A.; Mobasher, B.
Highlights: Wollastonite fibers were added at 5–15% of cement replacement levels. Effect of morphology, dosage, size of fibers on mechanical properties were studied. Fracture resistance curves show the region of stable crack growth in these systems. Flexural strength and fracture toughness could be enhanced by 40% and 150%. Toughening mechanisms such as crack bridging, and path deflection were observed. Abstract: Effect of mineral wollastonite micro and sub-micron fibers on the mechanical properties of cement-based systems are studied using compressive strength and notched beam flexural tests. A series of blended paste and mortar mixtures with silica fume and wollastonite particles of different morphology and size were developed and tested. Testing variables included four grades of wollastonite fibers or platelets with average particle size ranging from 33 to 2000 μm, with aspect ratios varying from 3:1 to 20:1, and cement replacement levels of 5%, 10%, and 15%, by mass. Non-linear fracture mechanics concepts used indicate considerable effect of wollastonite reinforcement on the fracture resistance of the cementitious matrix. Uniaxial compressive strength tests showed a 30% increase due to 10% cement replacement with wollastonite and silica fume. Flexural strength was enhanced by 40% and fracture toughness by as much as 150% at the optimal dosage of wollastonite fibers. Morphology of fractured surfaces was studied using SEM to correlate the mechanical properties with internal micro-structure. It was observed that at optimal dosage, wollastonite fibers promote classical toughening mechanisms such as crack bridging and crack path deflection.